Introducing A Family With Tens of Rare Craniofacial Clefts. Issue 5 (July 2019) - Kalantar-Hormozi, Abdoljalil; Abbaszadeh-Kasbi, Ali; Shalbaf, Shervin; Davai, Nazanin Rita
Abstract : Background: Craniofacial clefts are one of the rarest congenital malformations. When it comes to genetic inheritance patterns of craniofacial clefts, there are few studies on this subject due to the rarity and sporadic nature. In this study an extended family whose members have multiple craniofacial clefts has been introduced. Methods: The authors haphazardly found a family whose members have craniofacial clefts, either Tessier no. 0 or both Tessier nos. 0 and 14, and, consequently, they were categorized into 3 groups based on the severity of clefts. Results: Forty-two craniofacial clefts were noticed within the family. Twenty-two (52.3%) of patients were females and 20 (47.6%) were males. Twenty-three (54.8%) members had isolated Tessier no. 0 cleft, whereas 19 (45.2%) members had both Tessier nos. 0 and 14. Of all 42 patients, 18 (42.8%), 3 (7.1%), and 21 (50%) patients had severe, intermediate, and mild clefts, respectively. Conclusion: The present study reveals that in some patients genetic background is likely to be the cause of clefts. Abstract : Supplemental Digital Content is available in the text